The Effectiveness of Darask Platform as E-Learning Tool to Improve the Educational Process during COVID-19 - Abutaieh, Khaled; AlMohtadi, Reham; Almazaydeh, Laiali (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The globe is grappling with the COVID-19 pandemic, which has enslaved the economy, including the educational sector. This epidemic has caused recent changes and disruptions in all aspects of life, this pandemic has compelled educational systems all across the world to find altarenate methods to keep the process of education going on. To cope with the current case, Darasak platform is authorized by Jordanian Ministry of Education to be an alternative choice for proceeding with the educational process. The goal of the current study is to know the impact of Darasak platform to be compensate tool to perform the educational process during Covid 19. The data were collected by questionnaires and distributed by webs side to students, teachers and parents. The result of the study shown that Darasak platform was a new application to students so it was found that facilities, flexibility appropriateness and effectiveness of Darasak platform were not up to expectation. Students were not satisfied about the performance of Darasak platform.